Sacred Landscapes and Sustainable Tourism: Integrating Spirituality and Ecology in India (Journal of Informatics Education and Research, 2025)
The holy places of India, Himalayan pilgrimage routes and river banks, coastal temples, desert dharmah, Buddhist routes, Sikh dharam, and local groves of sanctuaries are both spiritual and ecological commons. This is a qualitative research paper that investigates the possibilities of practical integration of spirituality with ecological stewardship to sustain tourism in India. A multi- sited interpretive methodology based on document analysis, key-informant interview synthesis (published qualitative studies), and comparative case profiling (Varanasi -Ganga corridor; Kedarnath and the Char Dham; Meghalayas sacred groves; Sabarimala -Periyar; Ladakh monasteries; Amritsar Golden Temple; and the Puri -Chilika interface) forms the basis of developing a conceptual framework and a set of actionable design principles through the paper. Results are identified in five overlapping areas of leverage (1) culturally-grounded carrying capacity and ritual calendars; (2) community guardianship and equitable benefit-sharing; (3) sacred-water and sacred-forest protection with faith-based norms; (4) low-impact mobility and heritage-sensitive infrastructure; and (5) multi-faith governance to facilitate inclusive visitor experience. The paper includes a matrix of types of sacred-landscape, a stakeholder-instrument map, scenario-based impact pathways, and ends with an India-specific implementation roadmap aligned to SDG 8, 11, 12, 13, 14, and 15. The ministries, state boards, temple trusts, waqf boards, monastery councils, and destination managers are provided with policy and practice recommendations.